La ética y los estilos de liderazgo - Brito, Jorge G. (2016)
This study presents and compares different leadership styles, and makes note of the importanceof morals and ethics for business leaders. The author concludes that combining various aspectsand dimensions of the differing styles can help leaders to rise to meet challenges, and do so in anethical fashion.